1998
DOI: 10.1111/j.1469-7793.1998.487be.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of noradrenaline on intracellular pH in acutely dissociated adult rat hippocampal CA1 neurones

Abstract: 1. We examined the effects of noradrenaline on steady-state intracellular pH (pHé) and the recovery of pHé from internal acid loads imposed by the NHÚ¤ prepulse technique in hippocampal CA1 neurones acutely dissociated from adult rats. 2. Under nominally HCOצ-free conditions, acid extrusion was accomplished by a Na¤-dependent mechanism, probably the amiloride-insensitive variant of the Na¤-H¤ exchanger previously characterized in both fetal and adult rat hippocampal neurones. In the presence of external HCOצ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
49
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 48 publications
16
49
0
3
Order By: Relevance
“…Specifically, these researchers have suggested that manic and depressive states may be at least partially caused by the brain's attempts to correct this pH imbalance by causing an overactivation of monoaminergic systems, which has been known to increase pHi at least in hippocampal neurons. 53 Such a theory would also thus explain the more normalized pHi of bipolar patients in the manic and depressive states. 52 …”
mentioning
confidence: 99%
“…Specifically, these researchers have suggested that manic and depressive states may be at least partially caused by the brain's attempts to correct this pH imbalance by causing an overactivation of monoaminergic systems, which has been known to increase pHi at least in hippocampal neurons. 53 Such a theory would also thus explain the more normalized pHi of bipolar patients in the manic and depressive states. 52 …”
mentioning
confidence: 99%
“…BCECF-derived fluorescence emission intensities during excitation at 488 nm and 452 nm were at least 20-fold higher than the original GFP fluorescence signal. The dual excitation ratio method was used to estimate pH i employing a fluorescence ratio-imaging system (Atto Biosciences, Rockville, MD); full details of the methods employed have been presented previously (52,53). The high-[K ϩ ]/nigericin technique was employed to convert background-corrected BCECF emission intensity ratios into pH i values.…”
Section: Namentioning
confidence: 99%
“…Intracellular acid loads were imposed by exposing the cells for 2 min to NH 4 ϩ -choline solution. The recovery of pH i following an NH 4 ϩ pre-pulse was fitted to a single exponential function, and the first derivative of this function was used to determine the rate of change of pH i (dpH i /dt) at 0.05 pH i unit increments from the point of maximum acidification (52,53). Proton efflux was calculated by multiplying the measured dpH i /dt at a given pH i value by the intrinsic intracellular buffering capacity (␤ i ) at the same pH i value.…”
Section: Namentioning
confidence: 99%
“…It is expected that other channels or exchangers mediating cellular pH i changes could also give rise to relatively large pH i shifts beneath the plasma membrane. There is also potential for the feedback stimulation of pH regulatory mechanisms as a consequence of raised local cAMP levels (6,43,44) or the functional coupling of G protein-linked receptors to AC and acid extruders via divergent signaling mechanisms (45 Very significantly, however, we were able to prove that NHE1 was localized to the same subcellular compartments (caveolae) that expressed high levels of functional AC8. A similar distribution of NHE1 was also observed in membrane fractions from C6-2B glioma cells.…”
Section: Nhe1 Activity Protects Ac8 From Local Acid Shifts In Hek 293mentioning
confidence: 80%
“…However, it is now recognized that modest fluctuations in pH i can arise during "physiological" cellular activity (1)(2)(3)(4)(5)(6)(7)(8)(9). Furthermore, recent studies have provided evidence for pH i microdomains just beneath the plasma membrane, which can exhibit transient pH shifts on the order of several tenths of a pH unit, as a consequence of the local activity of plasma membrane transporters (10 -12).…”
Section: Intracellular Ph (Ph I )mentioning
confidence: 99%